Wisdom in the Poetry of Muḥmood Sami al Barodi - al Jaji, Khansa Muḥammad Dieb (Journal of Islamic and Religious Studies, 2017)
Muḥmood Sami al Barodi is a famous poet who was named the Resurrector of poetry in the early times when many poets of the old era were the cause of the decline in poetry. His poems had been studied from many aspects and by many scholars but no one ever spoke about al Barodi’s writings about wisdom. This article is focusing on the verses and poems that focus on the meaning of wisdom and everything that relate to it. He talked about the importance of wisdom in the poems as he encouraged the other poets to give attention to this meaning. Some published books and articles helped me write this article but I haven’t found any of them that gave this point enough significance though his poetry is full of verses about wisdom and so I chose to write about it.